2017
DOI: 10.1093/nar/gkx837
|View full text |Cite
|
Sign up to set email alerts
|

iSyTE 2.0: a database for expression-based gene discovery in the eye

Abstract: Although successful in identifying new cataract-linked genes, the previous version of the database iSyTE (integrated Systems Tool for Eye gene discovery) was based on expression information on just three mouse lens stages and was functionally limited to visualization by only UCSC-Genome Browser tracks. To increase its efficacy, here we provide an enhanced iSyTE version 2.0 (URL: http://research.bioinformatics.udel.edu/iSyTE) based on well-curated, comprehensive genome-level lens expression data as a one-stop p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 45 publications
2
95
0
1
Order By: Relevance
“…In addition to the dynamics of these lens-enriched genes, the present lens RNA-seq data also validates the “lens signature genes” previously identified by microarray analysis (Kakrana et al 2018). Indeed, the lens signature genes Aldoc , Dhx32 , Fabp5 , Gprc5b , Grifin , Gstm1 , Hmgn3 , Mboat1 , Mocs2 , Npl , Ogn , Pgam2 , Tmem40 and Zbtb8b are found to be highly expressed in the lens by the present analysis as well (Table S1).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…In addition to the dynamics of these lens-enriched genes, the present lens RNA-seq data also validates the “lens signature genes” previously identified by microarray analysis (Kakrana et al 2018). Indeed, the lens signature genes Aldoc , Dhx32 , Fabp5 , Gprc5b , Grifin , Gstm1 , Hmgn3 , Mboat1 , Mocs2 , Npl , Ogn , Pgam2 , Tmem40 and Zbtb8b are found to be highly expressed in the lens by the present analysis as well (Table S1).…”
Section: Resultssupporting
confidence: 85%
“…Recently, we demonstrated that for tissue-specific microarray datasets, an approach termed “ in silico WB-subtraction”, involving comparative analysis of the tissue in question to a “reference” WB dataset, provides estimates of tissue-specific enrichment that can be applied for prioritization of candidate genes. For the lens, we showed that tissue-enrichment is an excellent predictor of significance to lens biology, which has led to the identification and/or characterization of several new cataract-associated genes (Lachke et al 2012b; Anand and Lachke 2017; Kakrana et al 2018). Here, we tested the hypothesis that in silico WB-subtraction can be extended to process lens RNA-seq data and prioritize candidates important to lens biology and cataract.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations